On exact boundary controllability for linearly coupled wave equations - Bastos, W. D. [UNESP]; Spezamiglio, Adalberto [UNESP]; Raposo, C. A. (Academic Press Inc. Elsevier B.V., 2011)
In this paper we study exact boundary controllability for a system of two linear wave equations coupled by lower order terms. We obtain square integrable control of Neuman type for initial state with finite energy, in nonsmooth domains of the plane. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Boundary control; Exact controllability; Coupled wave equations; Double membrane-system